Assessment of the impact of the removal of cerebrospinal fluid on cerebral tissue volumes by advanced volumetric 3D-MRI in posthaemorrhagic hydrocephalus in a premature infant. Issue 5 (1st May 2003) - Hunt, R W; Warfield, S K; Wang, H; Kean, M; Volpe, J J; Inder, T E
Abstract : Current clinical practice in the premature infant with posthaemorrhagic ventricular dilatation (PHVD) includes drainage of cerebrospinal fluid (CSF). This case study used advanced volumetric three dimensional magnetic resonance imaging to document the impact of CSF removal on the volume of regional brain tissues in a premature infant with PHVD. The removal of a large volume of CSF was associated with an identical reduction in CSF volume, but more dramatically with a significant increase in the regional volumes of cortical grey matter and myelinated white matter. The alterations in cerebral cortical grey matter and myelinated white matter volumes may provide insight into the established association of PHVD with deficits in cognitive and motor functions.